Intervención de enfermería en la identificación de estilos de vida y la prevención de la hipertensión arterial en adultos mayores que asisten al centro de salud Enrique Ponce Luque. Babahoyo. Primer semestre 2018. - Palma Torres, Jessenia Katherine (2018)
Hypertension is a public health problem associated with an unbalanced lifestyle. For this reason, the continuous participation of nursing personnel is of paramount importance, who contribute in the task of educating users in improving the quality of life. The objective of the study was to determine how nursing interventions influence the lifestyle and prevention of hypertension in adults over 65 years of age who attend the Enrique Ponce Luque Health Center in Babahoyo Canton, first semester of 2018 A quantitative, descriptive, non-experimental, field study was carried out, cross-sectional to a sample of 60 older adults and 5 nursing professionals, using the inductive-deductive method and analysis-synthesis. Obtaining as results that 55% of older adults answered that the nurse always provided information about healthy eating, 63% responded that the nurse always guided them on how to lead a healthy lifestyle and 48% answered that the nurse provided information related to arterial hypertension and preventive measures Conclusions: The interventions of the nurse directly influence the lifestyle of older adults, because they are the nurses who maintain the first contact and identify the health situation and motivate self-care in the elderly through the care role and teacher.